Purification and Characterization of Laccase from Ceriporiopsis subvermispora - Wang, Chao; Xu, Hong; Jun Yun, Xue (Asian Journal of Chemistry, 2014)
Laccase from Ceriporiopsis subvermispora was purified and partially characterized using a combination of ammonium sulfate precipitation, DEAE-cellulose ion exchange chromatography and Sephadex G-100 molecular sieve column chromatography. The results demonstrated that the maximum laccase output from C. subvermispora fermentation reached 3900 U/L. The specific activity of the laccase increased from 10.28 U/mg in a crude enzyme solution to 245.27 U/mg after isolation and purification, with a purification factor of 23.86 and a yield of 24.40 %. The molecular mass of laccase was 63 kDa and the Michaelis-Menten constant value was 23.3 μmol/L. The optimal temperature for enzyme activity was 50 °C. The stabilization pH range was 4-5; within a pH 4-5 range, the relative activity was higher than 70 %.